Altered Brain Structure and Functional Connectivity of Primary Visual Cortex in Optic Neuritis - Huang, Jing; Duan, Yunyun; Liu, Sidong; Liang, Peipeng; Ren, Zhuoqiong; Gao, Yang; Liu, Yaou; Zhang, Xiaojun; Lu, Jie; Li, Kuncheng (Frontiers in Human Neuroscience, 2018)
This study aims to determine whether and how functional connectivity and gray matter volume alteration occurs in single attack and recurrent optic neuritis (ON) by using resting-state functional connectomics and voxel-based morphometry (VBM). Fifty-one patients with single attack ON (9 males, 42 females; mean age± SD: 37.51years ±13.03) and 45 patients with recurrent ON (13 males, 32 female; mean age± SD: 33.80 years ±13.93) were examined using structural MRI and resting-state functional MRI (RS-fMRI) sequences, and compared to 49 age- and gender-matched healthy controls (HC) (14 males, 35 females; mean age± SD: 33.57 years ±10.63). Functional connectivity (FC) analysis with a seed in primary visual cortex (V1 area) was used to assess the differences between these three groups. Whole brain gray matter atrophy was assessed using VBM. A correlation analysis was performed between FC results, structural MRI and clinical variables. This study provided imaging evidence of cortical neuroplasticity in both single attack and recurrent ON patients by using RS-fMRI.